The Effect of Diagenetic Evolution on Shale Gas Exploration and Development of the Longmaxi Formation Shale, Sichuan Basin, China - Wang, Jia; Tan, Xianfeng; Tian, Jingchun; Luo, Long; Gao, Xuanbo; Luo, Chao; Zeng, Chunlin; Zhang, Lei; Xue, Weiwei (Frontiers in Earth Science, 2021)
Diagenetic evolution is an important controlling factor of shale gas reservoirs. In this study, based on field outcrop and drilling core data, analytical techniques including X-ray diffraction (XRD), field emission scanning electron microscope combined with a focused ion beam (FIB-FESEM), and energy-dispersive spectroscopy (EDS) analyses were performed to determine the diagenetic evolution of the Longmaxi Formation shale and reveal the effect of diagenetic evolution on the shale gas exploration and development in the Sichuan Basin, Southwest China. The eodiagenesis phase was subdivided into two evolution stages, and the mesodiagenesis phase was subdivided into three evolution stages in the basin margin and center. Absorbed capacity and artificial fracturing effect of the Longmaxi Formation shale gas were related to mineral composition, which was influenced by sedimentary characteristics and diagenetic evolution. The diagenetic system in the basin margin was more open than that in the basin center due to a different burial history. The more open diagenetic system, with more micro-fractures and soluble constitute (e.g., feldspar), was in favor for the formation and preservation of secondary dissolved pores and organic pores in the basin margin. The relatively closed diagenetic system with stronger compaction resulted in deformation of pore space in the central basin.